Rancangbangun Sistem Informasi E-Booking Jasa Salon Berbasis Web - Purwatiningtyas, P; Ziana, Liana Rahma; Wahyudi, Eko Nur; Listiyono, Hersatoto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
The increasing development of information technology causes technology to play an important role in the progress of a company's business processes. This development also has an impact on salon business people. Salon is a place for hair and skin care to beautify your appearance. Meanwhile, currently many salons still use manual methods, namely queuing according to arrival when they want to be served, resulting in queues building up and data management also relying on the notebook method. Therefore, salons need a good booking system to improve customer service. The methodology used to build this system is the Waterfall model with stages of systems engineering, analysis, design, implementation and testing. The Web-Based Salon Services E-Booking Information System uses the PHP, XAMPP and MySQL programming languages as the DBMS to run the database. The Web-Based Salon E-booking Information System uses a database with 7 tables, namely admin, user, user role, category, service, booking, complaint. Based on testing and observations on the Web-based Salon E-booking Information System that has been created, it is concluded that the web-based salon E-booking information system is in accordance with what has been determined, namely in accordance with user needs. Meanwhile, the recommendation for a web-based e-booking information system for salon services is that this system can add a login feature for customers if the salon already has many customers and add a data back-up feature to avoid data loss if damage occurs to the storage system.